Kesatuan Transenden Agama-Agama dalam Perspektif Tasawuf (Kritik atas Pemikiran Frithjof Schuon) - Abdullah Muslich Rizal Maulana (Universitas Darussalam Gontor, 2014)
As one of the many themes that get a lot of attention on contemporary issues of Sufism is transcendent unity of religion from perspective of perennial philosophy. Perennial philosophy believes a universal and eternal unity of religion rest on its esoteric dimension. Esoteric dimension has it different concept with exoteric dimension, whereas esoteric dimension is inner dimension that spiritual, exoteric dimension is outer dimension of religions in the form of ritual, or other branches of the secondary nature of religions. This view would then imply the understanding of the validity of religious pluralism in the form of Sufism legitimacy. One of the figures was quite inspiring teachings perennial philosophy is Frithjof Schuon. Schuon, became one of the initiators of the transcendent unity of religions in the Sufism legitimacy that in its development and has a very strong relationship to the development of religious pluralism that is modern as are held by Chittick, Hick, or WC Smith. This paper will tries to analyze critically the origin of the transcendent unity of religions in the perspective of Sufism by arguing Frithjof Schuon.